Microbiology of sinusitis and the predictive value of throat culture for the aetiology of sinusitis - ÜLGER, NURVER; İLKİ, ZEYNEP ARZU (ELSEVIER SCI LTD, 2005)
A prospective study of throat cultures and maxillary sinus aspirates from children with chronic sinusitis (n = 21), acute sinusitis (n = 28) or a clinical diagnosis of chronic adenoiditis (n = 41) was performed. Seventy-two bacterial pathogens were isolated from sinus aspirates from 52% of the study population. Haemophilus influenzae was most common pathogen, followed by Moraxella catarrhalis, Streptococcus pneumoniae, Staphylococcus aureus, and group A streptococci. Quantitative throat cultures had positive predictive values of 41%, 53% and 75% for H. influenzae, Strep. pneumoniae and M. catarrhalis, respectively, while negative predictive values were 93-98%, indicating that these three pathogens do not cause sinusitis when absent from the throat.
Keywords: Children; Haemophilus influenzae; Moraxella catarrhalis; sinusitis; Streptococcus pneumoniae; throat cultures; COMMUNITY-ACQUIRED SINUSITIS; CHILDREN; THERAPY; GUIDE